Magnum photobook the catalogue raisonné - Ritchin, Fred; Naggar, Carole 1951- (Phaidon Press Limited, 2016)
The first complete illustrated bibliography of 1,000 iconic photobooks created by members of the renowned photo agency This fascinating in-depth survey brings Magnum's history alive through the genre of the photobook – an essential vehicle for photographers to share their work. Its pages include unpublished behind-the-scenes material, together with ephemera from the photographers' archives about the making of their books. With an introduction by Fred Ritchin and texts by Carole Naggar, this book explores the evolution of the photobook, as well as the important role that Magnum has played in the history of documentary photography.
Includes bibliographical references and index
Keywords: Magnum Photos Inc.; Geschichte 1938-2016; Photography, Artistic; Documentary photography; Fotografie; Fotobuch; Agentur; Fotograf; Henri Cartier-Bresson; Robert Capa; Steve McCurry; Bildband; Werkverzeichnis